An Early Crescent - Eric A. Winkel (International Institute of Islamic Thought, 1991)
An Early Crescent is about the exciting and greatly anticipated emergence of ideas which will inaugurate the rededication and renewal of Muslim effort and spirituality. It is about the process of intellectually taking charge of the environment and the discourse dominated by the West. There are two dimensions to this process of taking charge. One is the Islamization of Knowledge, and entails mastering the dominant idiom and then, from a position of strength and confidence, creating a uniquely Islamic paradigm in the field of knowledge. The second dimension recognizes that “discourse” is not just academic knowledge, but that discourse and knowledge are also inextricably tied into the environments and ecologies surrounding the Islamic community. The book is structured between the overview of Anwar Ibrahim and the epilogue of Abdullah Omar Naseef, two people deeply involved in contemporary politics, thinking, and policy making. Between this are writings about two dimensions of the process of taking charge of the dominant discourse, with the first part considering the Islamization of Knowledge and the epistemological characterization of the contemporary discourse, dominated as it is by the West, and the second part dealing with the way the dominant discourse configures the environment and ecology surrounding everyone in general, and the way it constrains the ummah specifically. Ziauddin Sardar‘s critique of the Islamization work plan centers around its veneer of positivism and the concommitant reification of the disciplines. Certainly there are overtones of positive theory building in the work plan, but it must also be remembered that the work plan is not designed to be revolutionary as much as corrective, and that it is aimed not so much at intellectuals as at students through the production of textbooks. And textbooks are certainly examples of knowledge-production. But no one who reads the impassioned prose of al Faruqi can imagine that here is a man who would simply pass an Islamic wand over the disciplines to Islamize them. On the contrary, his descriptions of contemporary Muslim alienation imply that we ...